FEATURES OF ORGANIZING OF GENERAL ACCOUNTING IN THE ASPECT OF PENSION INSURANCE SYSTEM IN CONDITION OF SUSTAINABLE DEVELOPMENT OF TAJIKISTAN - Abdurahmonova, Muqadamkhon Zokirkhonovna (UI Scholars Hub, 2022)
This article considered basic organizational aspects of general accounting of pension system in sustainable development condition of Republic of Tajikistan. Theoretical bases of pension system accounting are analysed. The key aspects of research work are based in the regulations confirmed on the “Instruction about general accounting organization and recording pension operations in accounting”. The problems of transformation of accounting and the pension system are pushing scientists to pay attention to the issues of organizing pension accounting. This scientific article is based on the research regarding to the theme of my candidate dissertation on theme: “Features of development and modernization of social insurance system in the national economy of Tajikistan”. This study should bring some clarity to the process of accounting for pension provision in Tajikistan in the context of sustainable development. To determine the general accounting organization features in the direction of the pension system, methods of analysis of definitions were used and the most frequently used accounting accounts were grouped. As a result of research work and studies of regulatory legal acts on accounting for pension provision, accounting entries were determined in accordance with international accounting standards in the context of sustainable development of Tajikistan. The theoretical foundations of accounting are determined, and the most used definitions of the investigated sphere are highlighted. In conclusion, it should be noted that to effectively organize the accounting of pensions, it is proposed to constantly improve the qualifications of accounting employees not only in the republic, but also in foreign countries that apply international accounting standards. Since the study of accounting from outside contributes to the correct organization and maintenance of modern pension accounting. The basic steps of social tax accounting in the context of sustainable development of Tajikistan are improved by author.